Hydrolysis of Waste Cooking Oil Using Rhizopus oryzae to Produce Free Fatty Acids - Muhamad Nur Rojab; Rintis Manfaati; Prans Connery Manurung; Keryanti Keryanti (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
Waste cooking oil is waste produced from palm oil after it has been heated and fried at high temperatures, and it can pollute the environment. One effort to reuse waste cooking oil is a fermentation processe that produces free fatty acids with the help of Rhizopus oryzae as a biocatalyst. Variations in initial substrate concentration ranged from 10 g/L to 70 g/L, followed by varied types of nitrogen sources, namely malt extract, beef extract, (NH2)2CO, NH4Cl, and (NH4)2SO4 at a concentration of 70 g/L to determine free fatty acid concentration. Fermentation was carried out for 7 days. The analysis carried out included the concentration of free fatty acids, biomass, and YP/X value. The optimum initial used cooking oil substrate was obtained at a concentration of 30 g/L with a YP/X value of 13.63%, a free fatty acid concentration of 2.13 g/L and a dry cell weight of 15.48 g/L. The best nitrogen source is beef extract with a Yp/x value of 11.78%, a free fatty acid concentration of 2.02 g/L and a dry cell weight of 17.0 g/L